Effects of Surface Charges on Dental Implants: Past, Present, and Future - Guo, Cecilia Yan; Matinlinna, Jukka Pekka; Tang, Alexander Tin Hong (International Journal of Biomaterials, 2012)
Osseointegration is a major factor influencing the success of dental implantation. To achieve rapid and strong, durable osseointegration, biomaterial researchers have investigated various surface treatment methods for dental subgingival titanium (Ti) implants. This paper focuses on surface-charge modification on the surface of titanium dental implants, which is a relatively new and very promising methodology for improving the implants’ osseointegration properties. We give an overview on both theoretical explanations on how surface-charge affects the implants' osseointegration, as well as a potential surface charge modification method using sandblasting. Additionally, we discuss insights on the important factors affecting effectiveness of surface-charge modification methods and point out several interesting directions for future investigations on this topic.